Collaborative Research Design Working with Business for Meaningful Findings (Springer Singapore, 2018)
This book articulates and interconnects a range of research methods for the investigation of business management processes. It introduces new directions that both recognise the business community as stakeholders in the research process and seek to include them in that process. The book presents a range of contemporary research methods with particular focus on those that allow insights into business managers' thoughts and behaviours. It includes fresh views on traditional research designs, for example new approaches to using literature reviews, experiments, interviews and observation studies. It also considers cutting-edge research methods, such as the use of vignettes, workshops, improvisation and theatre, as well as computer-based simulation. In addition to discussing new approaches to data capture and data generation, it presents new methods of data analysis by considering various forms of models and modelling, new forms of computer-aided text analysis and innovative approaches to data display. Finally, the book provides a link between the philosophical underpinnings of research and the different research methods presented. This is often neglected but undertaking the knowledge-generating journey that is research includes having a view on reality and marrying this to beliefs about how the reality to be investigated can be best expedited.